SUN TZU’S STRATEGY FOR WINNING THE SUSTAINABLE TOURISM MARKET - Putra, Dyan Triana; Marhendi, Mengku; Mistriani, Nina; Susilaningtyas, Gesit; Setyaningtyas, Margaretha (ITB AAS Indonesia Surakarta, 2024)
Abstract This research examines the effectiveness of adopting Sun Tzu's strategies to achieve domination in the tourism business, resulting in the establishment of sustainable tourism.